Gender inclusive sporting environments: the proportion of women in non-player roles over recent years - R Eime; M Charity; B. C Foley; J Fowlie; L. J Reece (BMC, 2021)
Abstract Background Throughout the ecosystem of sport, women have been and continue to be underrepresented at all levels compared to men. The capacity of community-level sport is heavily reliant on the many non-player roles including governance, as well as administration, coaching and officiating. Recently there has been increased attention to improving the gender balance in sport. The aim of this study is to investigate the proportions of women engaged in non-playing roles in sport (2016-2018). Methods This study involved secondary analysis of the AusPlay survey, a national population survey, funded by Sport Australia. This study utilised data from people aged 15-years or older about their involvement in non-playing roles in sport, and their demographic data. Survey respondents were asked "During the last 12 months, have you been involved with any sports in a nonplaying role, such as official, coach, referee, administrator, etc?" Analysis of non-player role responses focussed specifically on the top four non-player role categories; coach, official, administrator and manager. Frequency analysis concentrated on the distribution of men and women involvement in a non-player capacity for the three years, with detailed analysis of the most recent year (2018). Results In this study of 61,578 Australians there was a higher proportion of men in non-player roles in sport compared to women, across each of the three years (2018: men 55 %, women 46 %). Involvement of women in coaching increased significantly from 38 % to 2016 to 44 % in 2018 (p < 0.001). The proportion of women involved in administration roles significantly decreased from a peak of 51 % in 2017 to 46 % in 2018 (p < 0.001). Conclusions Aligned with strategic policy and investment strategies, there are gradual increased representation of women in non-playing sport, coaching roles. Women are still underrepresented in terms of coaches, officials and administrators, but are more likely to be managers. It is recommended that there is continued mentoring, identification and emphasising of female role models, and further strategies to increase female presence in non-playing roles. We recommend that future research, in line with appropriate gender and cultural-change theories, investigates and discusses the progress of gender equality throughout playing and non-playing role in sport.